Measuring Oral Vitamin B12 Bioavailability Using [13C]-cyanocobalamin in Humans. (29th May 2020) - Devi, Sarita; Pasanna, Roshni; Shamshuddin, Zeeshan; Bhat, Kishor; Sivadas, Ambily; Mandal, Amit; Kurpad, Anura
Abstract: Objectives: To biosynthesize a stable-isotope labeled [ 13 C]-cyanocobalamin and to measure its bioavailability in humans. Methods: Salmonella enterica was precultured in Luria-Bertani medium and single-cell colonies were grown in No carbon E medium, supplemented with [ 13 C]-ethanolamine as a sole-carbon source along with other precursors (dicyanocobinamide and dimethylbenzimidazole) and incubated for 48 h at 30°C and centrifuged. The pellets were resuspended in methanol/sodium cyanide and incubated overnight and extracts were purified by HPLC. The peaks corresponding to standard cyanocobalamin were collected and characterized by MALDI-MS. After animal testing, healthy young subjects were orally administered with [ 13 C]-cyanocobalamin in a protocol that included hourly blood sampling for 12 h post-dose, and daily sampling for the next 5 days, to characterize its kinetics at a higher dose than the daily requirement (∼10x, n = 4, 2 males and females) and its appearance was modeled using a two-compartment model with early and late absorption phases. The same model was applied for lower dose at daily requirement (∼2.5 μg, n = 11 males), with sampling for 12 h post-dose. In addition, the effect of co-ingested food (n = 1, male) and the effect of parenteral replenishment of existing body vitamin B12 stores by intramuscular injection of 1 mg hydroxocobalamin, (n = 3, males) on bioavailability was also studied. The appearance of tracer in plasma was quantified by Q-Exactive-Orbitrap-MS. Results: Biosynthesized [ 13 C]-cyanocobalamin was labeled with up to 7– 13 [C] atoms and at a daily requirement dose (∼2.5 μg), its mean bioavailability was 50.4 ± 8.2%, but this was also dependent on the existing body store of vitamin B12 . Two-weeks after replenishing the body stores, bioavailability increased by 1.5-fold (from 45.6 ± 0.02% to 67.8 ± 0.06%). At a higher dose (∼20 μg), its bioavailability was 6.0 ± 1.2% but the absolute amount absorbed was similar to that with the low dose. Conclusions: A novel stable isotope-based vitamin B12 bioavailability assessment is described at low and high doses. This has implications toward rationalizing dosages used in clinical supplementation and public health fortification programs. Funding Sources: Department of Biotechnology, India (to SD and AVK) and by the Wellcome Trust/DBT India Alliance Margdarshi Fellowshi p [No. IA/M/14/1/501, 681] awarded to AVK.